(untitled) (PETITUM, 2020)
This research aims to examine efforts to fulfill transitional justice through its four windows. The method used is normative legal research with conceptual and historical approaches. The results showed that the problem of impunity inhibited in all transitional justice windows, starting from the truth window in the absence of the Truth and Reconciliation Commission, the justice window in the form of a justice mechanism that caused friction between the National Human Rights Commission and the Attorney General’s Office, the reparation window which until now only Aceh and Palu have real programs for victims and survivors, institutional reform windows that have not reduced the total security approach and the absence of vetting mechanisms. Therefore, a policy reformulation process is needed in the Human Rights Court Law to strengthen the position of the NHRC and immediately discuss the TRC Bill, accelerate reparations and institutional reform programs Penelitan ini bertujuan untuk menelaah upaya pemenuhan keadilan transisi melalui empat jendela. Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan konseptual dan pendekatan sejarah. Hasil penelitian menunjukkan bahwa problem impunitas menghambat di semua jendela keadilan transisi, mulai dari jendela kebenaran berupa ketiadaan KKR, jendela keadilan berupa mekanisme peradilan yang menimbulkan friksi antara Komnas HAM dengan Kejaksaan Agung, jendela reparasi yang hingga saat ini baru Aceh dan Palu yang memiliki program yang nyata bagi para korban dan penyintas dan jendela reformasi institusi yang belum mereduksi total pendekatan keamanan serta ketiadaan mekanisme seleksi terhadap rekam jejak anggota militer. Oleh karena itu, dibutuhkan proses reformulasi kebijakan pada UU Pengadilan HAM dan segera membahas RUU KKR, percepatan program reparasi dan reformasi institusi.